2021
DOI: 10.1080/09540962.2021.1939584
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation going local: implementation, impacts and constraints from a German perspective

Abstract: The digital transformation of public administration is expected to fundamentally reshape the institutional setting of local service delivery, administration, and governance in Europe. Against this background, it is a cause for concern and criticism that the actual state of implementation, the impacts, and the hurdles faced at the local level of government have only scarcely been studied in public administration. The results of this study reveal several unintended and negative impacts of digital government refo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…In this study, we showed that a COVID-19-accelerated, more intensive use of digitalized communication tools has a positive effect on the effectiveness of local administrations. Our data thereby indicate that public institutions are able to adapt administrative structures to quickly evolving challenges during a crisis situation (as proposed by Kuhlmann and Heuberger 2021). Second, our data indicate that fastchanging environmental factors, such as legislation adjusted due to COVID-19, have a positive impact on the relationship between the use of digitalized communication tools and the administration's effectiveness.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, we showed that a COVID-19-accelerated, more intensive use of digitalized communication tools has a positive effect on the effectiveness of local administrations. Our data thereby indicate that public institutions are able to adapt administrative structures to quickly evolving challenges during a crisis situation (as proposed by Kuhlmann and Heuberger 2021). Second, our data indicate that fastchanging environmental factors, such as legislation adjusted due to COVID-19, have a positive impact on the relationship between the use of digitalized communication tools and the administration's effectiveness.…”
Section: Discussionmentioning
confidence: 52%
“…Within any organization, transformation, and change in the way it relates to its clients or users may be conditioned by the dimension of variables such as flexibility and the extent of bureaucracy it entails ( Connolly et al, 2018 ), and these variables could be relevant when implementing, or not, proposed changes to improve services provided by public administrations ( Hammi et al, 2018 ; Kuhlmann & Heuberger, 2021 ; Tangi et al., 2020 ). However, the aim of DT should be to increase agility and reduce the bureaucracy of organizational functions ( Marino-Romero, Palos-Sánchez, Velicia-Martin, et al, 2022 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the case of a DT process in an LG, size can be fundamental to achieving the proposed objectives when providing electronic resources for citizens (Catala´& Penalva, 2020;Ingrams et al, 2020;Morales & Sussy, 2018). In most cases, the dimension of the LG in its budget (Chua et al, 2022;Connolly et al, 2018;Kuhlmann & Heuberger, 2021) will condition the creation of a specific department to lead, supervise, and control the DT processes implemented (Jakob & Krcmar, 2018). However, the direction and importance of this influence have not always been addressed and analyzed in previous studies (Luna-Reyes et al, 2020).…”
Section: Facilitating Conditionsmentioning
confidence: 99%
“…The problem encountered by public administrations is that the implementation of new technologies requires institutional agreements to be approved by policy makers and this can delay the adoption process (Conradie and Choenni, 2014;Savoldelli et al, 2014). Other studies into digital administration have found obstacles for the implementation of technological tools due to a lack of confidence in technological devices (Twizeyimana and Andersson, 2019), the digital immaturity of the management of public institutions which, in turn, generates a greater workload and work stress (Kuhlmann and Heuberger, 2021), and the lack of security in the privacy and ownership of citizens' data (Schwester, 2009;Mergel et al, 2016). All of these require an adequate legal framework that clearly regulates the access and use of data and defines accountability.…”
Section: Negative Factors Of Technological Innovationmentioning
confidence: 99%